2009
DOI: 10.1016/j.jcrs.2009.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 2 types of silicone hydrogel bandage contact lenses after photorefractive keratectomy

Abstract: There were no differences in corneal reepithelialization or subjective measurements after PRK between the 2 types of silicone hydrogel bandage contact lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 15 publications
0
41
2
1
Order By: Relevance
“…The rate of wound healing is of great importance when considering a bandage contact lens material ensuring a faster healing process and less discomfort for the patient. [ 27 ] Specifi c investigation of the closed cell monolayers was undertaken by staining for zonal occludens-1 (ZO-1). The ZO-1 protein functions in the formation of tight junctions which are expressed around the cell membrane when a cell monolayer is intact and the epithelial barrier functioning.…”
Section: Doi: 101002/adhm201600258mentioning
confidence: 99%
“…The rate of wound healing is of great importance when considering a bandage contact lens material ensuring a faster healing process and less discomfort for the patient. [ 27 ] Specifi c investigation of the closed cell monolayers was undertaken by staining for zonal occludens-1 (ZO-1). The ZO-1 protein functions in the formation of tight junctions which are expressed around the cell membrane when a cell monolayer is intact and the epithelial barrier functioning.…”
Section: Doi: 101002/adhm201600258mentioning
confidence: 99%
“…Eyes bandaged with higher transmissibility lenses also achieved significantly better visual acuity and had reduced haze for up to a month [130]. Combining these outcomes with those from studies using lens pairs of more modest differential transmissibility [131][132][133], suggests that similar benefits might accrue down to at least 110 barrers/cm; although inconsistent specification of Dk/t among some of these reports does introduce additional uncertainty.…”
Section: Bandage Lensesmentioning
confidence: 99%
“…9 They found no statistically significant difference in terms of re-epithelisation degree and pain levels. Engle et al reported that corneal re-epithelialization after PRK was faster with less subjective complaints within the first 48 hours with lotrafilcon-A BCL compared to those with hydrogel BCL.…”
Section: 910mentioning
confidence: 89%
“…9 The aim of using BCL is to increase patient comfort by reducing pain induced by ocular irritation. Gıl-Casorla et al study was unable to determine a statistically significant difference concerning patient answers to questions intended at determining subjective complaints.…”
Section: 910mentioning
confidence: 99%